A comprehensive toolkit for protein localization and functional analysis in trypanosomatids - Paterou, Athina; Sáez Conde, Julia; Týč, Jiří; Sunter, Jack Daniel; Vaughan, Sue; Gull, Keith; Dean, Samuel (Open biology, 2025)
African trypanosomes are medically important parasites that cause sleeping sickness in humans and nagana in animals. In addition to their pathogenic role, they have emerged as valuable model organisms for studying fundamental biological processes. Protein tagging is a powerful tool for investigating protein localization and function. In a previous study, we developed two plasmids for rapid and reproducible polymerase chain reaction-based protein tagging in trypanosomes, which enabled the subcellular mapping of 89% of the trypanosome proteome. However, the limited selection of fluorescent protein tags and selectable markers restricted the flexibility of this approach. Here, we present an extended set of >100 plasmids that incorporate universal primer annealing sequences, enabling protein tagging with a range of fluorescent, biochemical and epitope tags, using five different selection markers. We evaluated the suitability of various fluorescent proteins for live and fixed cell imaging, fluorescent movies, and we demonstrate the use of tagging plasmids encoding tandem epitope tags to support expansion microscopy approaches. We show that this series of plasmids is functional in other trypanosomatid parasites, significantly increasing its value. Finally, we developed a new plasmid for tagging glycosylphosphatidylinositol-anchored proteins. We anticipate that this will be an important toolset for investigating trypanosomatid protein localization and function.
Keywords: Protein Transport; expansion microscopy; plazmidy; Animals; toolkit; zvířata; Humans; transport proteinů; trypanosomatid; Protozoan Proteins; protozoální proteiny; Trypanosoma brucei brucei; Plasmids; protein tagging; trypanosome; lidé; Trypanosomatina